PENERAPAN KONSELING BEHAVIORISTIK TEKNIK KONTRAK PERILAKU UNTUK MENGATASI DISFUNGSIONAL PROKRASTINASI AKADEMIK SISWA - Ilham Khoerul Imam; Sumarwiyah Sumarwiya; Nur Mahardika (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The aims of this study are: 1. To find out the factors that cause dysfunctional academic procrastination in class XI Agribusiness Food Crops and Horticulture (ATPH 4) SMKN 1 Maja Academic Year 2020/2021. 2. Overcoming the dysfunctional academic procrastination of class XI (ATPH 4) students of SMKN 1 Maja for the 2020/2021 academic year.The type of research used in this research is case study research. The subjects studied were students of class XI (ATPH 4) VRS and RRS class XI of SMKN 1 Maja for the academic year 2020/2021 who experienced dysfunctional academic procrastination. The analysis used in this research is inductive analysis. The data analysis method in this study was carried out systematically starting from the process of data collection, clarification, description, and interpretation of each part.By using behavioristic counseling, behavioral contracting techniques can result in changes in the counselee's behavior to be able to start working on tasks, be able to complete tasks, be fast in doing assignments, and be able to collect assignments on time and prioritize doing tasks above other activities.